Effects of oral moisturizing gel containing propolis following head and neck radiotherapy: randomized controlled pilot trial - Ryoma Nakao; Takao Ueno (Nature Publishing Group, 2021)
Abstract Aim Topical administration of oral gel may reduce radiotherapy-related oral complications. The aim of this study was to examine clinical and microbiological effects of self-administration of different gel formulations to oral mucosa in head and neck cancer patients. Materials and methods Twenty-seven subjects were recruited from outpatients who underwent radiotherapy of at least 50 Gy to the head and neck area. They were randomly assigned to oral gel with the following different ingredients: placebo, chlorhexidine, curry leaf, propolis, and turmeric. Before and after intervention, oral symptoms were evaluated, and nine oral pathogens in saliva were also quantified using real-time PCR. Results Twenty-five subjects completed the study and their data were analyzed. The number of Porphyromonas gingivalis in saliva significantly decreased after treatment with propolis gel, but not after any other treatments. Propolis gel treatment also relieved oral pain in all subjects who had oral pain at the baseline. Conclusions Topical administration with propolis gel may not only reduce P. gingivalis carriage in saliva, but also relieve oral pain. Discussion A future larger-scale clinical trial of oral propolis gel is needed to determine its clinical efficacy in radiotherapy-related oral complications of head and neck cancer patients.